1994
DOI: 10.1177/00957984940202004
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Africentric Values, Self-Esteem, and Black Identity on Drug Attitudes among African American Fifth Graders: A Preliminary Study

Abstract: The relevance of Africentric values and beliefs has been articulated by a number of African American scholars. Moreover, Africentric frameworks have been used in the design and implementation of substance abuse prevention programs. The purpose of this study was to investigate the role of Africentric values along with self-esteem and Black identity on drug attitudes amongfifth graders. Measures of Africentric values, self-esteem, and Black identity were obtained from 54 African Americanfifth graders. A regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
61
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 14 publications
6
61
0
Order By: Relevance
“…Helms (1990) noted that racial identity "is a sense of group or collective identity based on one's perception that he/she shares a common racial heritage with a particular racial group" (p. 3). A growing body of evidence demonstrates the importance of a salient racial identity as a psychosocial protector in both mental health functioning and health risk behaviors such as substance use (Belgrave et al, 1994;Brook, Balka, Brook, Win, & Gursen, 1998;Caldwell, Zimmerman, Bernat, Sellers, & Notaro, 2002; Klonoff & Landrine, 1999;Scheier, Botvin, Diaz, & Ifill-Williams, 1997;Sellers, Caldwell, Schmeelk-Cone, & Zimmerman, 2003). Although research in this area is still emerging, it is generally accepted that a less salient racial identity is associated with poorer outcomes, whereas a strong and positive group affiliation is related to more positive outcomes.…”
mentioning
confidence: 99%
“…Helms (1990) noted that racial identity "is a sense of group or collective identity based on one's perception that he/she shares a common racial heritage with a particular racial group" (p. 3). A growing body of evidence demonstrates the importance of a salient racial identity as a psychosocial protector in both mental health functioning and health risk behaviors such as substance use (Belgrave et al, 1994;Brook, Balka, Brook, Win, & Gursen, 1998;Caldwell, Zimmerman, Bernat, Sellers, & Notaro, 2002; Klonoff & Landrine, 1999;Scheier, Botvin, Diaz, & Ifill-Williams, 1997;Sellers, Caldwell, Schmeelk-Cone, & Zimmerman, 2003). Although research in this area is still emerging, it is generally accepted that a less salient racial identity is associated with poorer outcomes, whereas a strong and positive group affiliation is related to more positive outcomes.…”
mentioning
confidence: 99%
“…An Africentric worldview is expected to foster attitudes and behaviors that are intolerable of drug use and abuse (Belgrave et al, 1994;Long, 1992;Nobles & Goddard, 1992). According to Nobles and Goddard (1992), an African model of alcohol, tobacco, and drug prevention for African American families should be used to create and guide programs, activities, and practices that will enable African American families to resist drug use and manage the drug problems facing the African American community.…”
Section: Africentric Worldview and Drug Attitudes And Behaviorsmentioning
confidence: 99%
“…Gary and Berry (1984) found that church involvement was associated with attitudes intolerant of drugs. Belgrave et al (1994) conducted a preliminary study which examined the influence of Africentric values, self-esteem, and Black identity on drug attitudes among African American fifth graders. Participants included 54 African American fifth graders attending an urban elementary school.…”
Section: Africentric Worldview and Drug Attitudes And Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence that salient racial identity is a psychosocial protector in mental health functioning and health risk behaviors (Belgrave et al, 1994;Brook, Balka, Brook, Win, & Gursen, 1998;Caldwell, Zimmerman, Bernat, Sellers, & Notaro, 2002;Klonoff & Landrine, 1999;Scheier, Botvin, Diaz, & Ifill-Williams, 1997;Sellers, Caldwell, Schmellk-Cone, & Zimmerman, 2003). Numerous researchers have argued that racial identity is a multidimensional construct (Gonzales & Cauce, 1995;Phinney, 1992;Romero & Roberts, 1998;Rotheram-Borus, Lightfoot, Moraes, Dopkins, & LaCour, 1998;Sanders-Thompson, 1994;Sellers, Smith, Shelton, Rowley, & Chavous, 1998;Smith, Walker, Fields, Brookins, & Seay, 1999;Stevenson, 1994).…”
Section: Racial and Ethnic Identity And Engagement In Violent Behaviorsmentioning
confidence: 99%